The Influence of Contextual Teaching and Learning (CTL) Learning Approach on Mathematical Reasoning Ability of Class VIII Students of SMP Negeri 3 Pematangsiantar. - Samosir, Nanda Laura; Siahaan, Theresia Monika; Sauduran, Golda Novatrasio (Lembaga Riset Mutiara Akbar, 2022)
Mathematical reasoning ability is one of the learning objectives that are expected to develop optimally in students. But in reality, students' mathematical reasoning abilities cannot always be achieved by students optimally. This is also found in class VIII SMP Negeri 3 Pematangsiantar. One of the factors that causes this to happen is the lack of trained students to use and develop mathematical reasoning skills properly. One of the efforts that can be done to improve students' mathematical reasoning abilities is to apply a contextual teaching and learning approach. The purpose of this study was to determine whether the mathematical reasoning ability of students who used a contextual teaching and learning approach was better than the mathematical reasoning abilities of students who used conventional learning in class VIII of SMP Negeri 3 Pematangsiantar. The type of research used was a quasi-experimental design with a posttest only control design. design. The population in this study were eighth grade students of SMP Negeri 3 Pematangsiantar. Sampling was done by random sampling technique. Class VIII-7 was selected as the experimental class and class VIII-8 as the control class. The research instrument used was a final test sheet in the form of description questions to see students' mathematical reasoning abilities. Based on the analysis of the results of the final test of students' mathematical reasoning abilities, it was concluded that mathematical reasoning abilities by learning using a contextual teaching and learning approach were better than learning using conventional learning, which could be seen at an error rate of 5%. This shows that there is an influence on students' mathematical reasoning abilities. The average test for the experimental class is 82.63 and the control class is 60.59